Never let you go - Murphy, Monica, 1970- (Bantam Books, 2016)
"Perfect for readers of Colleen Hoover, Jay Crownover, and K.A. Tucker, the second novel in this darkly sexy contemporary series from bestselling author Monica Murphy wraps up an emotionally powerful two-part tale of forbidden love. The truth hurts, they say--and my pain cuts deep. While I was falling for Ethan, he was deceiving me the entire time. He held a huge secret, protected by his lies. When I discovered what he was hiding, the truth shook my world, threatening to ruin us forever. Ruin me. But I soon realized that what we share can't be destroyed. The connection between us is too strong. It always has been. I can't deny him any longer. And I can't deny my truth: I'm in love with Ethan. I don't want to let him go. While we're trying our best to make this relationship work, other forces are fighting against us. My family, who wants to keep me safe. The media obsessed with my tragic past. The public that feeds off of it. Even Ethan's father--the man who nearly destroyed me all those years ago. He's doing his best to finish the job. Despite my love for Ethan, the doubts creep in, clouding my mind. Is he worth the pain? Will our love survive, or will we have no choice but to end it--end us--once and for all? Praise for Monica Murphy's Never Tear Us Apart "All the best parts of romance and betrayal. I couldn't turn the pages fast enough."--New York Times bestselling author Jay Crownover "A powerful story that left me raw yet hopeful."--USA Today bestselling author K.A. Tucker "A powerful story of friendship, trauma, coping and betrayal. The characters jump off the page into real life and will have readers gasping and feeling every emotion that they go through. Another amazing book to add to Murphy's already stellar library!"--RT Book Reviews (4 1/2 stars) "Murphy has written a compelling and emotional love story of two severely broken people, each of whom can be healed only by the other."--Booklist "Murphy imbues these characters with genuineness and plausibility. [Readers] will look forward to the promised sequel."--Publishers Weekly "It's poetic, addresses difficult themes, and captures the essence of our fragility as humans and the strength love provides."--Heroes and Heartbreakers"--